A contribution to the improvement of milking and working conditions on Serrana goat farms in Northeastern Portugal - Barbosa, José Carlos (2005)
This presentation is about milking and working conditions on Serrana goat farms in Trás- os-Montes, a region of northeastern Portugal. The Serrana goat is an indigenous breed and is generally raised to produce milk for cheese-making. Goats are hand-milked inside their shelters. There are no places specifically for milking nor special equipment or facilities to do this work. In collaboration with ANCRAS (Portuguese Serrana breeders' association), we developed a project with the aim of improving milking and working conditions on Serrana goat farms, bearing in mind the socio-economic conditions of breeders. We propose the use of a milking platform with a self-locking barrier in order to improve the posture of milkers and the efficiency of milking. Our study compared traditional manual milking with manual milking using such a platform and barrrier. The use of this equipment can improve milking and working conditions on the goat farms of the region.